IL17A Depletion Affects the Metabolism of Macrophages Treated with Gemcitabine - Cecilia Roux; Gianluca Mucciolo; Joanna Kopecka; Francesco Novelli; Chiara Riganti; Paola Cappello (MDPI AG, 2021)
Background: Interleukin (IL)17A is a member of the IL17 cytokine family, which is released by both immune and non-immune cells such as tumor and stromal cells into the tumor microenvironment. IL17 receptors are also widely expressed in different type of cells. Among all the members, IL17A is the most controversial in regulating tumor immunity. Here, we investigated how IL17A inhibition modulated macrophage differentiation and metabolism in the presence or absence of gemcitabine. Gemcitabine is the gold standard drug for treating pancreatic cancer and can increase macrophage antitumoral activities. Results: We observed some unique features of macrophages polarized in the absence of IL17A, in terms of RNA and protein expression of typical phenotypic markers, and we demonstrated that this paralleled specific changes in their metabolism and functions, such as the induction of an antitumor response. Interestingly, these features were almost maintained or enhanced when macrophages were treated with gemcitabine. We also demonstrated that the anti-IL17A antibody effectively reproduced features of macrophages derived from IL17A knock-out mice. Conclusion: Overall, we provide a proof-of-concept that combining an anti-IL17A antibody with gemcitabine may represent an effective strategy to modulate macrophages and enhance the anti-tumor response, especially in pancreatic cancer where gemcitabine is widely used.